Study of Mobile Internet Security Risk and End-to-End Service Security Evaluation - Rong Yue; Hong Li (Dianxin kexue)
The mobile internet architecture and its security risks were introduced.Then the index system of evaluation was discussed,which mainly included confidentiality,integrity,availability,reliability,safety and performability.In the end,a method was proposed for evaluating end-to-end service security.